PENGARUH KOMUNITAS PEGIAT KOTA LAMA TERHADAP PERKEMBANGAN VITALITAS KAWASAN KOTA LAMA SEMARANG - Larasati Larasati; Isti Andini; Ana Hardiana (ARSITEKTURA, 2016)
Semarang old city area is one of the historical district in Indonesia. Semarang old city area was forgotten and abandoned, but it shows progress of condition of its vitality. It is inseparable from the existence of the old city community who has concern the sustainability of the Semarang old town area. The aims of this research are to identify the condition and vitality progress, identify the characteristic of the community and to identify the influence of the community intervention to the area. This research is using quantitative descriptive method supported by analytical techniques such as descriptive analysis to determine the characteristics of community interventions in the area and analysis of simple paired t-test to determine the progression of its vitality. Next, the results of earlier analyzes will be identified by using descriptive explanatory analysis techniques. The results show that Semarang old city area has a significant progress in terms of nine variables vitality assessment indicators. Community intervention in the old city area more on the implementation of the activities and included in the category of active intervention. Therefore, it can be argued that the interventions made by the community influence the progression of the vitality that occur the old city area of Semarang in the last five years, especially in attracting visitors to the old town area of Semarang.Keywords: Vitality area, Semarang Old Town